1837 Ala. Laws 7 - (:unkn) unknown (My University, 1837)
§ 2: Imposed tax of $100 on any person selling, giving, or disposing of any Bowie knife or Arkansas toothpick. Failure to pay the tax was subject to penalty of perjury.
Keywords: TAX - NON-GUN ARMS